Daily heat stress in Kraków in the warm period 2012–2022 based on hourly meteorological measurements and radiative fluxes derived from satellite systems - Wieczorek , Joanna; Bochenek , Bogdan; Strzyżewski, Tomasz; Hajto, Monika J.; Sekuła , Piotr; Bokwa , Anita; Zimnoch , Mirosław (Acta Geographica Lodziensia, 2024)
This paper aims to present an assessment of the hourly structure of the thermal environment in the warm period of the year. Special attention was paid to the conditions potentially resulting in heat stress for citizens of Kraków’s central district. Two approaches were used to analyse the hourly data: 1) a criterion of thermal threshold >30°C, as potentially generating heat stress, which is included in meteorological warnings issued in Poland, and 2) a criterion based on physiological responses described by the value of the Universal Thermal Climate Index (UTCI) >32°C, which corresponds to conditions of strong heat stress for the human thermoregulatory system. The data of basic meteorological characteristics of one-hour timespan resolution from measurements in AGH station located at Reymonta Street in Kraków covering the period 2012–2022 were adopted in the study. Shortwave direct and diffuse and longwave radiation fluxes corresponding to the station’s location grid were derived from the Eumetsat LSA SAF MSG satellite remote-sensing system and used for Mean Radiant Temperature (Tmrt) and UTCI hourly calculations. Thermal environment conditions expressed by Tair ≥30°C, which could lead to heat stress, occurred in less than 2% of hourly terms (931 from 47,044) in the months April–September in the 11-year period. Far more terms were assessed as “with adverse conditions leading to heat stress”: 2,215 cases when UTCI≥32°C. In view of the above, it is worth highlighting that more than half of the negative and oppressive weather conditions resulting in heat stress may be neglected in risk assessments and predictions using only the basic thermal criterion.